2017
DOI: 10.1155/2017/3615707
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanoparticles Based Electrochemical Biosensor Strip for Detection of Japanese Encephalitis Virus

Abstract: We reported a disposable and sensitive electrochemical biosensor strip based on carbon nanoparticles modified screen-printed carbon electrode (SPCE) for rapid and sensitive detection of Japanese Encephalitis Virus (JEV). Amino group functionalized carbon nanoparticles were prepared from preformed chitosan nanoparticles. Japanese Encephalitis Virus (JEV) antibody was immobilized onto the surfaces of carbon nanoparticles through amide bonds formation between amino groups of carbon nanoparticles and carboxylic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
(31 reference statements)
0
29
0
Order By: Relevance
“…Which improves electron transfer efficiency. In addition, the amino group on the surface of CNPs enable the attachment of antibody ( Lai et al, 2017 ). Later, AgNPs was used to modify SPCE, and investigated by EIS analysis concerning JEV.…”
Section: Electrochemical Biosensors For Virus Detectionmentioning
confidence: 99%
“…Which improves electron transfer efficiency. In addition, the amino group on the surface of CNPs enable the attachment of antibody ( Lai et al, 2017 ). Later, AgNPs was used to modify SPCE, and investigated by EIS analysis concerning JEV.…”
Section: Electrochemical Biosensors For Virus Detectionmentioning
confidence: 99%
“…The majority of publications are devoted to registration of the resultant current of the redox probe corresponding to changing electrode potential. Ferri/ferrocyanide, ferrocene, ferrocenethanol systems, and ruthenium complexes are the most frequently used redox probes [50,69,70]. The electrochemical behavior of redox probes depends on the receptor layer and the biosensor operating principle.…”
Section: Voltammetry Amperometrymentioning
confidence: 99%
“…Chin and co-workers successfully applied CNPs for conjugation with JEV antibody and detection of JEV in human serum samples on a SPCE, with LOD of 2 ng/mL [121]. Another research group also modified a SPCE by CNPs for rapid and sensitive detection of JEV in human serum, with an LOD of 0.36 ng/mL [70]. Figure 6 depicts the preparation of the electrochemical biosensor for the detection of JEV with using CNPs as an immobilization platform for the JEV antibody [70].…”
Section: Electrochemical Biosensors For Jev Diagnosticmentioning
confidence: 99%
“…They showed that the smartphone reader had a hardware which connected to the back of a smartphone and provided the user with an interface to handle the operation, communicate with cloud services and acquire test results, and also developed a safe cloud service for the tele-monitoring of results (Natesan et al, 2019). Carbon-NPs-modified screen-printed carbon electrode (SPCE)-based electrochemical biosensor strip for rapid and sensitive detection of the Japanese Encephalitis Virus (JEV) was developed by Lai et al (2017). Hamdy et al (2018) developed an ultrasensitive AuNPs biosensor functionalized with thiol-linked oligonucleotides, which could recognize conserved RNA standards of foot and mouth disease virus (FMDV).…”
Section: Nanotechnology-based Techniquesmentioning
confidence: 99%